ANALISIS YURIDIS SERTIFIKAT TANAH HAK MILIK ELEKTRONIK(E-CERTIFICATE) DEMI MEWUJUDKAN KEPASTIAN HUKUM - Novita Riska Ratih (International Significance of Notary, 2021)
Permasalahanbuktikepemilikanhakatastanah di Indonesia mendorongpemerintahterusberinovasidalammenerbitkansertifikathakmilik. Inovasi yang dilakukanadalahmengubahdarisertifikat analog menjadielektronik. Sertifikathakmilikatastanah yang semula diterbitkan dalam bentuk cetak kertas berlembar-lembar, dilengkapi dengan hologram berlogo BPN untuk menghindari pemalsuan sertifikat. Namun kenyataannya, permasalahan yang dihadapi saat ini adalah banyaknya kasus sertifikat ganda, yang berujung pada permasalahan hukum sengketa tanah sangat marak terjadi di Indonesia hingga kini. Pemerintah mengeluarkan aturan baru tentangsertifikatelektroniksebagaibuktisahkepimlikantanah. Peraturan Menteri Agraria/ Badan Pertanahan Nasional Nomor1/2021memberikandampakpengembanganbagihukumpembuktianapabilaterjadisengktaataskepemilikantanah. Harapannyadapatmenjadisolusi atas permasalahan sengketa pertanahan karena semuanya sudah tersistem secara elektronik serta memudahkan masyarakat dalam pengurusan hak milik tanah.            Penelitianinimenggunakanpendekatan yuridis normatif dengan menggunakan sumber bahan hukum primer dan sekunder. Metode pengumpulan bahan hukum menggunakan studi kepustakaan. Fokusdalampenelitianinimeliputi: pengaturan pendaftaran hak atas tanah menurut Permen ATR/BPN Nomor 1 Tahun 2021 Tentang Sertifikat Elektronik, dan kekuatan hukum sertifikat tanah hak milik elektronik dalam hukum positif di Indonesia.            Kesimpulan yang bisa diambil dari penelitian ini adalah PP No. 24/1997, PMNA No. 3/1997 dan Permen ATR/BPN No. 1/2021 akan berlaku berdampingan dalam mengaturpengadministrasiantanah yang didaftarkan. Namun, saatinimengalamikendalakarena proses pendaftarantanahmasihbelumselesaisemuanya. Hal tersebutberakibat pada kurangmemadainyakeutuhan data fisik dan yuridistanahsehinggadapatmenghambatpenggunaan e-sertifikatsebagaialatbuktihukum. Syaratsupayasertifikatelektroniksahsebagaibuktihukumharusmemilikiinformasih yang utuh, akuntabel, dan dapatdisajikandalamsistem digital. Hasil cetak dari Informasi dan Dokumen Elektronik menurut ‘Pasal 5 Permen ATR/BPN No.1/2021’, merupakan perluasan  alat  bukti  surat  yang diatur dalam ‘Pasal 184 (1)  KUHAP dan alat bukti tertulis sesuai Pasal 1866 KUH Perdata’.Kata kunci : Sertifikat Elektronik, AnalisisYuridis, Kepastian Hukum Certificatee of land rights is valid as a strong evidence as confirmed in Article 19 paragraaph (2) letter C of Basic Agrarian Law and Article 32 pargraph (1) of ‘Government Regulation No. 24/1997 on Land Registration. The land certificate was originally issued in the form of sheeted paper printing, equipped with a hologram bearing the BPN logo to avoid falsification of certificates. However, the problems faced in reality is that the cases of dual land certificates, which eventually resulted in land disputes legal issues are very rampant in Indonesia until now. The government issued a new regulation on land ownership evidence, Minister Regulation of ATR / BPN No. 1/2021 concerning Electronic Certificates. This rule will change the form of land certificates or paper-based land books into electronic land certificates whose data are included in the system. The presence of this electronic certificate is expected to be a solution to the problem of land disputes because everything has been systemized electronically and can facilitate the community in the process of managing property rights on land.            The approaching method used was juridical normative by using primary and secondary legal material sources. Methods of collecting legal materials used literature studies. There are two problems. namely: the registration of land rights according to Minister Regulation ATR/BPN No. 1/2021 on Electronic Certificate,and the legal force of electronic property certificate in Positive Law in Indonesia.            Conclusions that can be drawn from this study are Government Regulation No. 24/1997, PMNA No. 3/1997 and Minister Regulation ATR/BPN No. 1/2021 will apply sidee by side in the implementaation of land registration. Due to the implementation of land registration in Indonesiaa has not been fully registred, so physical and juridical dataa for each area of land is not yet fully avaiilable. Electronic certificate can be as a means of electronic evidence if the information integrity can be guaranteed, can be accounted for, can be accessed and can be displayed through the Electronic System so as to explain a situation. The printout of Electronic Information and Electronic Documents according to Article 5 Minister Regulation ATR/BPN No.1/2021, is an extension of the proof of mail as stipulated in Article 184 (1) of Criminal Code Procedure (KUHAP) and written evidence in accordance with Article 1866 of the Civil Code (KUHP)Keywords : Electronic Certificate, Yuridical Analysis, Legal Certainty